Pyometra - Yolanda, Dimas Satria (Fakultas Kedokteran Universitas Andalas, 2019)
Background : Pyometra is a rare condition with an incidence ranging from 0.01 - 0.5% among all gynecological patients.2 Pyometra is known to be rare in the general population and is more common in elderly women.3 In postmenopausal elderly patients, the incidence increases to 13.6% .4. The classic triometry of pyometra is postmenopausal bleeding, purulent vaginal discharge, and lower abdominal pain,Objective : Report the handling of pyometra casesCase Report : reportedly a 73-year-old woman came to the ER of RSUP Dr. M. Djamil on December 10, 2018 at 14.30, a referral from BMC Padang hospital with a diagnosis of abdominal pain susp. intraabdominal tumor. Ultrasound examination showed the uterus in normal size which was not in accordance with the picture of pyometra. Laparotomy with adhesionolysis and aspiration of pus in the patient was performed. This is appropriate for evacuating the pyometra mass in this case.Conclusion : In this case, to overcome the infection and evacuate the masses. The recommended antibiotics are broad-spectrum antibiotics, such as penicillin, piperacillin tazobactam, imipenem, meropenem, metronidazole, and vancomycin. Mass evacuation can be done by laparotomy or curettage accompanied by cervical dilatation.Keywords: Pyometra, pascamenoupose